Gold standards framework annual meeting. Improving end of life care using gold standards framework. Issue 1 (1st June 2011) - Thomas, K; Stobbart-Rowlands, M
Abstract : Over the last century the way we die has changed and there has been a growing awareness and consideration of end-of-life care as a society. Now, we have the chance to live longer with serious illnesses, to live in the context of our dying, to plan our end-of-life care, to consider the kind of life and death we wish to have through advance care planning discussions – highlighting and improving this further is the purpose of this ACPEL conference. In England, the challenge of improving end-of-life care for all was moved a step-change further by the comprehensive NHS End of Life Care Strategy (2008), helping to mainstream end-of-life care within health and social care. The Strategy supported introducing advance care planning discussions early, and recommended that 'every organisation involved in providing end of life care will be expected to adopt a coordination process such as the Gold Standards Framework (GSF)'. GSF is an evidence based whole system approach, that aims to improve the quality, coordination and organisation of care leading to better patient outcomes in line with their wishes. It incorporates advance care planning as a key step in the process of integrated delivery. The wide range of training programmes run from the National GSF Centre, enable generalist frontline staff to provide quality care for people nearing the end of life, providing teaching, tools, evaluations, resources and guidance. An update will be provided during the session. The GSF Training Programmes includes those in Primary Care (basic GSF established 2000 and widely used by most GP Practices), care homes/long term facilities, Acute Hospitals, Domiciliary Care, Community Hospitals, spiritual care etc. The new practice-based distance-learning Next Stage GSF programme 'Going for Gold' was launched to improve primary care further. Over 2000 care homes have undertaken the 9–12 month practical GSFCH Training and up to 200 homes/year are accredited. The Acute Hospital programme is in its second phase, with benefits demonstrated, but many challenges. One of the key ways forward in future will be the integration of such coordinating frameworks involving frontline generalist providers across boundaries of care, to provide seamless integrated consistent support using a common language. Some examples of best practice using GSF will be described and some planned developments described.